2011
DOI: 10.1021/bm200039s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dendron Cross-Linked PEG Hydrogels as Corneal Adhesives

Abstract: In pursuit of a wound-specific corneal adhesive, hydrogels formed by the reaction of propionaldehyde, butyraldehyde, or 2-oxoethyl succinate-functionalized poly(ethylene glycol) (PEG) with a peptide-based dendritic cross-linker (Lys3Cys4) were characterized. These macromers react within minutes of mixing to form transparent and elastic hydrogels with in vitro degradation times that range from hours to months based on the type of bonds formed during the cross-linking reaction – either thiazolidine or pseudoprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 66 publications
1
47
0
Order By: Relevance
“…Current clinical practice involves suturing the cornea; however, this practice increases the potential for postoperative complications such as infections, astigmatism, corneal scars (sometimes necessitating further corneal procedures), and postsurgical cataracts. 31 Finally, through engineering the crosslinkers, degradation time for this adhesive could be tuned between hours and months. An ideal adhesive is considered to adhere to the moist corneal surface, rapidly seal the wound, restore intraocular pressure (IOP), maintain eye structural integrity, have a refractive index close to native cornea, be biocompatible and elastic, maintain a microbial barrier, and be bioabsorbed during tissue regeneration.…”
Section: Corneal Woundsmentioning
confidence: 99%
“…Current clinical practice involves suturing the cornea; however, this practice increases the potential for postoperative complications such as infections, astigmatism, corneal scars (sometimes necessitating further corneal procedures), and postsurgical cataracts. 31 Finally, through engineering the crosslinkers, degradation time for this adhesive could be tuned between hours and months. An ideal adhesive is considered to adhere to the moist corneal surface, rapidly seal the wound, restore intraocular pressure (IOP), maintain eye structural integrity, have a refractive index close to native cornea, be biocompatible and elastic, maintain a microbial barrier, and be bioabsorbed during tissue regeneration.…”
Section: Corneal Woundsmentioning
confidence: 99%
“…By esterifying the dendrimers with succinic acid monomethylallyl ether, and photochemically polymerizing the alkenes, soft gels were produced [213]. These materials are used as corneal adhesives [215,216] and for cartilage repair [217,218]. Scheme 51.…”
Section: The Use Of Other Aliphatic Dendronsmentioning
confidence: 99%
“…[78][79][80] In a recent study, the properties of hydrogels prepared from the reaction of a peptide dendron (Lys3Cys4) with three different types of homobifunctional aldehyde-terminated PEG macromers: PEG-propionaldehyde (P-Ald PEG), PEGbutyraldehyde (B-Ald PEG), and PEG-2-oxoethyl succinate (E-Ald PEG) were studied in order to investigate the properties of pseudoproline or thiazolidine linkages. 81 The adhesive strength of P-Ald hydrogels was weaker than the B-Ald and E-Ald hydrogels and its degradation was shown to be within hours of cross-linking, while the degradation times of B-Ald and E-Ald hydrogels were 1.5 and 24 weeks, respectively. It was also shown that the cysteineterminated Lys3Cys4 dendron reacted with the butyraldehyde poly ethylene glycol (BPEG) upon mixing to form a thiazolidine linkage, which is susceptible to hydrolysis.…”
mentioning
confidence: 94%